A digitális korszak orosz prózairodalmának tendenciái: az interaktív irodalom kérdéséhez - Csernyak, Marija (Studia Litteraria, 2020)
The paper focuses on the analysis of e-literature, which is also present in contemporary Russian literature. It defines e-literature as a modern cultural phenomenon which heavily builds upon the readers’ activity and choices, as well as interactivity. It reviews the characteristics of e-literature and its place in today’s literature, primarily based upon Mikhail Epstein’s theories. The article introduces the genre diversity and potentials of e-literature through one of the most characteristic works in Russian e-literature, Boris Akunin’s Octopus project.